Evaluating the advantages and disadvantages of thorium-based nuclear power plants - Yüksel, Serhat; Dinçer, Hasan; Çağlayan, Çağatay; Mikhaylov, Alexey; Yavuz, Duygu (Emerald Group Publishing Ltd., 2023)
Nuclear energy is of vital importance for the energy independence of countries. Therefore, some of the countries have given priority to nuclear energy investments. However, there are some risks in nuclear reactors. For this reason, some countries are uneasy about nuclear energy investments. Thorium-based nuclear power plants are also recommended to minimize these risks. It is possible to talk about many advantages of these power plants. However, there are some negative aspects to these investments. In this study, both positive and negative aspects of thorium-based nuclear power plants are discussed simultaneously. In this context, first, the literature was comprehensively examined, and seven different factors were determined. An analysis is then carried out using the DEMATEL method. It is concluded that the cost and uncertainties have the greatest weight. In addition, suitability and physical and chemical reasons are other significant items. The results obtained show that thorium-based nuclear power plants are not very efficient now. In this context, the costs of thorium-based nuclear reactors should be reduced by new research and development activities. Otherwise, the high-cost problem reduces the efficiency of these reactors. With the developing technology, it is necessary to reduce the high costs. If the costs cannot be reduced, financial sustainability of thorium-based nuclear reactors will not be possible, although there are many benefits.
Keywords: Clean Energy; Energy; Energy Markets; Energy Risks; Green Energy; Nuclear Energy; Renewable Energy Sources; Risk Assessment; Technological Innovations; Thorium